EXPLORING THE THERAPEUTIC POTENTIAL OF UMBILICAL CORD MESENCHYMAL STEM CELLS IN MODULATING TROPHOBLAST CELL FUNCTION FOR PREGNANCY-RELATED PLACENTAL DISORDERS - Dr. Praveen Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Preeclampsia and intrauterine growth restriction are disorders caused by dysfunctional trophoblast cells during pregnancy. Unfortunately, trophoblast cell function is little improved by treatments that target it. In addition to their ability to self-renew, to differentiate into a variety of cell types, and to possess paracrine properties, umbilical cord mesenchymal stem cells (hUCMSCs) have a number of immunomodulatory properties, making them a potential source for cell therapy. We used hUCMSC supernatants or cocultured hUCMSCs with trophoblast cells to determine whether hUCMSCs could influence trophoblast cell functions. A remarkable difference existed between the two treatments in terms of trophoblast cells’ migration and invasion capacities, as well as their ability to proliferate. As well, hUCMSCs modulated the levels of hCG, PIGF, and sEndoglin in trophoblast culture medium when a concentration of hUCMSCs is applied. Through improving trophoblast cellular functions, hUCMSCs may be used to treat pregnancy-related placental diseases.